O mercado de trabalho visto pela lente do direito da concorrência - Lima, Leda Batista da Silva Diôgo de (2023)
Antitrust and labor market were traditionally seen as worlds apart until very recently. Contributing to this distance was the perception that they represented completely different values (on the one hand, human labor as a vehicle for promoting human dignity; on the other, free market and free competition) and the presumption that labor markets were highly competitive. However, studies conducted especially from 2010 onwards began to call into question several of these assumptions: it was noticed that labor markets are not as competitive as imagined, that wages have not accompanied the increase in productivity of recent years, that information asymmetries and search costs highly contribute to the vulnerability of workers with low bargaining power. Although common sense has disseminated a negative perception about the correlation between competition and labor, with the former often pejoratively seen as promoting unlimited economic growth, this Dissertation reflects on the following question: can Competition Law aid the sustainable development of labor relations when applied to curb potential anticompetitive effects in the labor market? The answer to this question goes through three stages. First, it will aim to situate the problem and discuss why it is important to review labor market dynamics from a competition standpoint, discussing the role of Competition Law in the binomial economic growth-human development by identifying the negative effects caused by monopsony power. Then, through a bibliographic review, it will map the thematic evolution in a comparative perspective and review relevant local jurisprudence in order to evaluate the state of the art of the discussion, identifying that the application of antitrust to labor market dynamics is relatively rare. Based on these findings, it intends to systematize which labor dynamics may be relevant to the study of Competition Law and it will problematize that recognizing the jurisdiction of Brazilian competition authorities over certain labor markets dynamics involves reflecting upon the expansion of the traditional role of competition, the existence of corporate social responsibility and the effects of such jurisdiction. Methodologically, the research is instrumented through an extensive bibliographical review of the hypothetical-deductive method of approach and the technique of indirect documental research. The theme was chosen for its legal and social relevance, given that the absence of legal provisions and consolidated case law opens up space for abuses that can negatively impact the employee's situation, which is particularly aggravated by the unequal Brazilian reality.